Development of Sciber Applications (Screening with Special Needs) Funding for Learning Innovation and Assistive Technology (Assistive Technology) for Students with Special Needs in Higher Education - Restian, Arina Restian; Arifin, Bustanol; Deviana, Tyas; Suwandayani, Beti Istanti; Kuncahyono, Kuncahyono; Herviani, Vivi Kurnia (Jurnal Pendidikan Kebutuhan Khusus, 2023)
This research aims to produce Sciber Application products (Screening with Special Needs). with Special Needs) for Regular Students and Students with Special Needs, 3) Will produce creative innovations in SCIBER Application Assistive technology (Screening with Special Needs) for Regular Students and Students with Special Needs. Based on the results of product development found a very high validity of 98% with the final product data with findings that the media is easy to use, the media provides benefits in good self-assessment, the media contains very high interactivity, the media is in accordance with the goals of media development, and the design is very attractive in Public trial at Muhammadyah University Malang